CONCEPT OF TRADITIONAL PERFORMANCE AND ITS MEANING - Daughter of Murodova Durdonakhan Rayimjon; Yusupjonova is the daughter of Dilfuzakhan Olimjon; Anvarova is the daughter of Barnokhan Dilshodjon (Scholars Digest Publishing, 2023)
In this article, information is given about the traditional performing arts that are forming in our country, one of its directions - dutor performing arts.
Keywords: traditional music, classical music, oral creativity, dutor instrument.